Determinants Analysis of Manufacturing Companies Values Listed On the Indonesia Stock Exchange - Paramitha Anggraeny; Hendri Hermawan (Profesional Muda Cendekia Publishing, 2021)
The purpose of this study is to describe the effect of profitability, size, leverage, and dividend policy of manufacturing companies for the period 2015-2017 on firm value. The research method in this study uses a quantitative approach with SPSS analysis tools. This research was conducted on the Indonesia Stock Exchange with secondary data in the form of the Annual Report of Manufacturing Companies for the 2015-2017 Period. Based on the purposive sampling criteria in this study, there were 47 manufacturing companies consisting of 19 sub-sectors of the company that were sampled in this study. The results of the analysis show that the variable that most influences firm value is profitability. Dividend policy has an effect on firm value. Leverage affects firm value. Because investors are very careful when they want to invest their funds in the company. So it can be concluded that investors are very concerned about the company’s debt before they make an investment. Firm size has no effect on firm value. Therefore, the value of a manufacturing company cannot be measured only based on the size of the company’s assets.